Financialisation and demand and growth regimes: A review of post-Keynesian contributions - Eckhard Hein; Till van Treeck (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
We review post-Keynesian assessments of the macroeconomic demand and growth impacts of financialisation. First, we examine the channels of influence of financialisation on distribution and on the different components of private aggregate demand, i.e. investment, consumption and net exports. Since increasing shareholder power and shareholder value orientation of management has been viewed as key to understanding the macroeconomics of financedominated capitalism, we start with the effects of financialisation in the context of the postKeynesian theory of the firm and explain the other channels from there. An important result is the emergence of 'profits without investment' demand and growth regimes, for which we point out the condition based on Kalecki's profit equation. The third section then turns to the post-Keynesian analysis of the different variants of 'profits without investment' demand and growth regimes in finance-dominated capitalism. We review the different levels of analysis, the national income and financial accounting de-composition approach as well as different attempts at identifying growth drivers. We argue that these different levels of analysis are complementary for our understanding of demand and growth regimes under financialisation.
Keywords: E12; E21; E22; E25; E44; 330; Financialisation; demand and growth regimes; stagnation; post-Keynesian distribution and growth models